Fine-scale foraging segregation in a green turtle (Chelonia mydas) feeding ground in the Bijagós archipelago, Guinea Bissau - Madeira, Fernando Miguel; Rebelo, Rui; Catry, Paulo; Neiva, João; Barbosa, Castro; Regalla, Aissa; Patrício, Ana Rita (Frontiers in Marine Science, 2022)
Green turtles (Chelonia mydas) are highly dependent on neritic foraging areas throughout much of their life. Still, knowledge of recruitment dynamics, foraging habits, and habitat use in these areas is limited. Here, we evaluated how the distribution and food preferences of green sea turtles from different life stages varied within a foraging aggregation. We focused on two islands in Guinea-Bissau, Unhocomo and Unhocomozinho, using water captures and survey dives to record habitat use and characteristics, and stable isotopes to infer diet. Additionally, we used stable isotopes to infer their diet. Two habitat types were sampled: deeper (2.26 ± 0.4 m) rocky sites fringed by mangrove with macroalgae, and sandy shallows (1.37 ± 0.12 m) surrounded by rocky reefs with macroalgae and seagrass. The two benthic communities were similar isotopically and in terms of species composition, except for the presence or absence of seagrass, which had unique signatures. We captured 89 turtles ranging from 35 cm to 97 cm in curved carapace length (i.e., juvenile to adult stages). Size distribution was habitat-dependent, with most smaller turtles present in sandy shallows and larger turtles favoring slightly deeper rocky sites. Turtle isotopic signatures differed between the habitat of capture, regardless of size, revealing a marked dichotomy in foraging preference. All turtles fed primarily on macroalgae, mostly rhodophytes. However, individuals captured in sandy habitats had evident seagrass skewed isotopic signatures. Larger turtles may be unable to use the more diverse shallower foraging sites due to increased vulnerability to predation. Despite the proximity of the sampled foraging sites (2.7 km apart), the two foraging subgroups seem to maintain consistently different feeding habits. Our study highlights how heterogeneous green turtle foraging habits can be within populations, even at small geographic scales.